From dusk till dawn - Are nights a dangerous time for hospital admissions? - Corinna Hentschker (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
This paper addresses the question whether patients have a higher risk of death if they are admitted to a hospital during the night rather than during the day. Since hospital resources are reduced at nights, night admissions might be more dangerous. The empirical analysis is based on matching. Although the results show that patients admitted during the night have a higher risk of death, sensitivity analyses suggest, that this result is likely to be driven by unobserved patient heterogeneity.
Keywords: I11; I19; 330